Penerapan knowledge sharing dengan media Portal Binus di Bina Nusantara University - Syifa Naufal Qisty (Faculty of Communication, Padjadjaran University, 2021)
With the development of information technology, document management is now done digitally and paperless. Document management is also carried out as an implementation of knowledge sharing activities in an organization. Document management as a part of knowledge sharing activities is one of which is carried out by Bina Nusantara University (Binus). This article is compiled to find out how document management is an implementation of knowledge sharing in the Binus University environment. The method used is descriptive method of conducting interviews and literature review. From the research conducted, Binus University developed the Binus portal as a forum for employees to carry out knowledge sharing activities as well as manage documents in the organization. The managed documents include institutional documents such as organizational structure documents, business processes, duties and functions of each directorate, training materials, references in carrying out assignments, sharing expertise, case studies, case-based reasoning, as well as documents in the form of ideas, innovations, and opinions written in popular form by employees at Binus.